The dimension intentional of the Pragmatic of the acts of speech in the Qur'anic discourse - Al Qarni, Sharifa Ahmed Hassan; Babsil, Aisha Saleh Ahmed (Journal of Humanities & Social Sciences, 2019)
This research aimed to highlight the concept of willfulness in the pragmatics lesson of the speech acts in a trial to find out its relationship with Arabic pragmatics related to the Qur’anic discourse. It also discusses differences in the Arabic and westerns viewpoints about the concept. Results revealed that Arabs had the lead in identifying the concept of willfulness and its significance in Islamic discourse analysis. However, results also revealed that both sides pinpointed that discourse is primarily a communicative willful act that cannot be achieved without the linguistic tradition. Such linguistic tradition constitutes the reciprocal knowledge of the interlocutors. The research also concluded that validity is the core of discourse and that turns the articulation into a meaningful speech.
Keywords: pragmatics; verbs of speech; intent; Quranic discourse; fundamentals of jurisprudence; linguistic custom